Las insuficiencias del marxismo crítico y los problemas del mundo contemporáneo - Mansilla, H. C. F. (Nómadas. Critical Journal of Social and Juridical Sciences, 2005)
Based on almost unkown literature in German language and publications from Eastern Europe, the author retraces the evolution of so-called western or critical marxism, since the beginning around Rosa Luxemburg and Eduard Bernstein until the revisionist marxism which ended altogether with the collapse of communism in 1989. There is a stress on the truly original approaches of Karl Korsch and Georg Lukács. The main thesis: even marxist dissidents did not thoroughly unterstand the main problems of today, because the core of marxism cannot question modernity, ecological problems and the idolatry of technique and economic-material development.